2023
DOI: 10.1136/bmjopen-2023-073397
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and physical fitness among children and adolescents after the onset of the COVID-19 pandemic in the WHO European Region: a systematic review protocol

Helena Ludwig-Walz,
Waldemar Siemens,
Sarah Heinisch
et al.

Abstract: IntroductionThe implementation of COVID-19 pandemic-related restrictions resulted in limitations for physical activity (PA) opportunities, which may have initiated a longer-term behavioural change. The protocol describes the methodology for a planned systematic review that aims to summarise changes in PA and physical fitness (PF) in children and adolescents in the WHO European Region after the onset of the COVID-19 pandemic.Methods and analysisThe protocol adheres to the ‘Preferred Reporting Items for Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Although we cannot rule out that other clinical factors are responsible for physical inactivity in some patients, this finding highlights the importance of applying behavior change techniques to adolescents. As studies indicate that measures to contain the COVID-19 pandemic have had negative impacts on PA among European children and adolescents [ 38 ], this becomes all the more important. However, negative effects of pandemic-related restrictions were not reflected in the level of self-reported PA in our patients, at least until 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot rule out that other clinical factors are responsible for physical inactivity in some patients, this finding highlights the importance of applying behavior change techniques to adolescents. As studies indicate that measures to contain the COVID-19 pandemic have had negative impacts on PA among European children and adolescents [ 38 ], this becomes all the more important. However, negative effects of pandemic-related restrictions were not reflected in the level of self-reported PA in our patients, at least until 2022.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review and meta-analysis is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) [ 17 ] statement (Additional file [AF 1 ]: Table S1) and adheres to the Cochrane Handbook for Systematic Reviews [ 18 ]. It was registered on the International Prospective Register of Systematic Reviews (PROSPERO; CRD42023395871) [ 19 ] and an a priori protocol was published [ 20 ]. Deviations from the protocol are reported in AF 1 : Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…We designed the search strategy by using validated or recommended search filters and conducted a peer-review process considering the evidence-based Peer Review of Electronic Search Strategies (PRESS) checklist [ 22 ] (see protocol [ 20 ] for further details). The search strategy for every database is presented in the Supplement (AF 1 : Table S4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations